The relationship between structural and functional differences of the lumbar multifidus and structural brain morphology in females with non-specific low back pain: An observational study - Rahmat Adnan; Evy Dhondt; Lieven Danneels; Tine Willems; Sophie Van Oosterwijck; Jessica Van Oosterwijck (PLoS ONE, 2025)
No earlier study investigates the relationship between the structure and function of lumbar multifidus (LM) and gray matter thickness (GMT) and grey matter volume (GMV) in the regional cortical areas that are related to sensorimotor control in patients with NSLBP and in healthy controls (HCs). This study asseses LM morphology such as muscle and fat cross sectional area (CSA), and muscle fat index (MFI) with T1-weighted Dixon. Muscle functional MRI (mfMRI) was used to assess T2-rest and T2-shift of the LM muscle and cortical GMV and GMT derived from high resolution T1-weighted images. Linear mixed models were used to analyze these relationships. This study revealed positive associations between MFI of the LM and GMV of the paracentral and postcentral cortices were found, irrespective of LBP. Positive associations were found between T2-rest of the LM muscle at multiple lumbar levels, GMT (Rostralmiddlefrontal, caudalmiddlefrontal, precentral, superiorpariental, postcentral) and GMV (rostramiddlefrontal, caudalmiddlefrontal, postcentral, supramarginal, rostralanteriorcingulate). GMT of the caudalmiddlefrontal cortex and posteriorcingulate cortex was positively associated with T2-rest at LL L4 of LM and UL L4 of LM, respectively. A significant negative association was observed between the T2-shift of the LM at UL L4 and GMT of the supramarginal cortex. Negative associations were observed between T2-shift of LM at LL L4 and GMV of the rostralmiddlefrontal and paracentral cortex irrespective of LBP. Our result emphasize that altered LM function and structure in NSBLP and HC, and its associations with altered brain structural properties.